Alcohol reduction outcomes following brief counseling among adults with HIV in Zambia: A sequential mixed methods study. - Mah Asombang; Anna Helova; Jenala Chipungu; Anjali Sharma; Gilles Wandeler; Jeremy C Kane; Janet M Turan; Helen Smith; Michael J Vinikoor; for IeDEA Southern Africa (Public Library of Science (PLoS), 2022)
Data from sub-Saharan Africa on the impact of alcohol on the HIV epidemic in sub-Saharan Africa is limited. In this region, it is not well understood how people with HIV (PLWHA) respond to alcohol reduction counseling while they are linked to HIV clinical care. We conducted an explanatory sequential mixed-methods study to understand patterns of alcohol use among adults (18+ years) within a prospective HIV cohort at two urban public-sector clinics in Zambia. At antiretroviral therapy (ART) start and one year later, we measured alcohol use with Alcohol Use Disorders Identification Test-Consumption (AUDIT-C) and those reporting any alcohol use were provided brief counseling. We conducted focus groups at 1 year with participants who had any alcohol use and 20 in-depth interviews among the subgroup with unhealthy use pre-ART and who either reduced or did not reduce their use by 1 year to moderate levels or abstinence. Focus group Discussions (FGDs) (n = 2) were also held with HIV clinic staff. Qualitative data were analyzed using thematic analysis. The data obtained from 693 participants was analyzed (median age 34 years, 45% men), it revealed that unhealthy alcohol use (AUDIT-C >3 for men; >2 for women) was reported among 280 (40.4%) at baseline and 205 (29.6%) at 1 year on ART. Reduction from unhealthy to moderate use or abstinence was more common with older age, female, non-smoking, and at Clinic B (all P<0.05). Qualitative data revealed ineffective alcohol support at clinics, social pressures in the community to consume alcohol, and unaddressed drivers of alcohol use including poverty, poor health status, depression, and HIV stigma. Healthcare workers reported a lack of training in alcohol screening and treatment, which led to mixed messages provided to patients ('reduce to safe levels' versus 'abstain'). In summary, interventions to reduce unhealthy alcohol use are needed within HIV clinics in Zambia as a substantial population have persistent unhealthy use despite current HIV clinical care. A better understanding is needed regarding the implementation challenges related to screening for unhealthy alcohol use integrated with HIV services.